Vitrification of Mouse MII Oocyte Decreases the Mitochondrial DNA Copy Number, TFAM Gene Expression and Mitochondrial Enzyme Activity - M Amoushahi; M Salehnia; SJ Mowla (JRI, 2017)
Background: The objective of this study was determination of the changes in the reactive oxygen species (ROS) level, mitochondrial DNA (mtDNA) copy number and enzyme activity and transcription factor A (TFAM) gene expression in oocytes after vitrification. Methods: The oocytes at metaphase II (MII) stage (n=320) were collected from superovulated adult female mice (n=40). These oocytes were divided into vitrified and non-vitrified groups (n=160 in each group). After vitrification of oocytes, ROS level, mtDNA copy number; TFAM gene expression and mitochondrial enzymes activity (cytochrome C oxidase and succinate dehydrogenase) were assessed and compared with non-vitrified group. Visualization of the mitochondria was done using Mitotracker green staining under confocal microscope. Data were compared by independent T-test. Values of p<0.05 were considered as statistically significant. Results: The survival rate of oocytes after vitrification and warming was 96.05%.  The intensity of cytochrome C oxidase activity, mtDNA copy number and TFAM gene expression in non-vitrified oocytes were significantly lower and the level of ROS was higher in vitrified oocytes in comparison with non-vitrified group (p<0.05). But the intensity of succinate dehydrogenase activity was not significantly different between the two groups. The pattern of mitochondrial distribution in two groups of study was similar but the intensity of Mitotracker green in non-vitrified oocytes was significantly higher than vitrified oocytes (p<0.05). Conclusion: This study showed that vitrification of mouse MII oocytes reduced the mtDNA copy number and mitochondrial cytochrome C oxidase activity by increasing ROS level, thus the subsequent embryo development may be affected.